Cultural travel and migrancy the artistic representation of globalization in the electronic media of West Java - Jurriens, Edwin 1972- (Verhandelingen van het Koninklijik Instituut voor Taal-, Land-en Volkenkunde, 2004)
It describes artistic approaches to globalization, one of the problems that has benn felt most pressing during the late New order and early Reformation. Situating itself at this remarkable turning-point in Indonesian history, it shows that local artists have not been mere victims or products of globalization, but virtual migrants who self-consciously steer the electronic media on their worldwide travels. The book gives an analysis of relevant case-studies and historical debates on culture and representation in Indonesia and the West, and also provides a overview of early developments and recent trends in the Indonesian and West Javanese media landscapes. With its focus on Sundanese language and culture, it is a pioneering and gab-filling complement to the existing literature on media, which has predominantly dealt with national and international, rathe than regional or local, cultural contexts.